A Microporous Anionic Metal–Organic Framework for Sensing Luminescence of Lanthanide(III) Ions and Selective Absorption of Dyes by Ionic Exchange. Issue 19 (27th March 2014) - Qin, Jun‐Sheng; Zhang, Shu‐Ran; Du, Dong‐Ying; Shen, Ping; Bao, Shao‐Juan; Lan, Ya‐Qian; Su, Zhong‐Min
Abstract Herein, a novel anionic framework with primitive centered cubic (pcu) topology, [(CH3)2NH2]4[(Zn4dttz6)Zn3]⋅15 DMF⋅4.5 H2O, (IFMC‐2; H3dttz=4, 5‐di(1H‐tetrazol‐5‐yl)‐2H‐1, 2, 3‐triazole) was solvothermally isolated. A new example of a tetranuclear zinc cluster Zn4dttz6 served as a secondary building unit in IFMC‐2. Furthermore, the metal cluster was connected by ZnII ions to give rise to a 3D open microporous structure. The lanthanide(III)‐loaded metal–organic framework (MOF) materials Ln3+@IFMC‐2, were successfully prepared by using ion‐exchange experiments owing to the anionic framework of IFMC‐2. Moreover, the emission spectra of the as‐prepared Ln3+@IFMC‐2 were investigated, and the results suggested that IFMC‐2 could be utilized as a potential luminescent probe toward different Ln3+ ions. Additionally, the absorption ability of IFMC‐2 toward ionic dyes was also performed. Cationic dyes can be absorbed, but not neutral and anionic dyes, thus indicating that IFMC‐2 exhibits selective absorption toward cationic dyes. Furthermore, the cationic dyes can be gradually released in the presence of NaCl.